Can test construction account for varying gender differences in international reading achievement tests of children, adolescents and young adults? – A study based on Nordic results in PIRLS, PISA and PIAAC. Issue 1 (2nd January 2018) - Solheim, Oddny Judith; Lundetræ, Kjersti
Abstract: Gender differences in reading seem to increase throughout schooling and then decrease or even disappear with age, but the reasons for this are unclear. In this study, we explore whether differences in the way 'reading literacy' is operationalised can add to our understanding of varying gender differences in international large-scale surveys. We first compare the impact of gender on reading literacy in PIRLS 2011 (10-year-olds), Programme for International Student Assessment (PISA) 2009 (15-year-olds) and Programme for the International Assessment of Adult Competencies (PIAAC) 2012 (16–24-year-olds), respectively, across the Nordic countries. Then we compare how reading literacy is operationalised in those surveys. We find similar patterns of gender differences across the Nordic countries, with the largest effect sizes in PISA and the smallest in PIAAC. Further, even though the three surveys define reading literacy in similar ways, they operationalise and assess that construct differently. The magnitude of the observed gender differences appears to be associated with certain assessment features including text type, item format, aspects of reading and implementation.